THE EFFECTIVENESS OF INFORMATION SERVICES USING SELF MANAGEMENT TECHNIQUES TO REDUCE STUDENT PROCRASTINATION IN LEARNING IN CLASS X MIA STUDENTS AT MUHAMMADIYAH 01 SMA MEDAN - Fatanah, Amrina; Hasibuan, M. Fauzi (BRIGHT VISION Journal of Language and Education, 2024)
This research aims to determine the description of student procrastination in learning at Muhammadiyah 01 Medan High School students. The purpose of this research is to describe the difference in scores in reducing student procrastination in learning among experimental group students before and after being given information service treatment using self-management techniques. Meanwhile, the control group was given treatment before and after being treated with information services. This research is quantitative research with an experimental research type. The objects of this research were class X MIA students at SMA Muhammadiyah 01 Medan. The data collection technique in this research used a questionnaire to students to determine students' procrastination in learning. The results of this research show that students have high levels of procrastination in learning, resulting in students' inability to control their time while studying, especially in the school environment and while studying. The analysis test results used the Wilcoxon Signed Ranks Test and the Kolmogorov Smirnov Two Independent Samples analysis test. Thus, based on the results of research conducted, among others: (1) there is a significant difference in student procrastination in learning in the experimental group before (pretest) and after (posttest) with information services using self-management techniques. (2) there is a significant difference in student procrastination in learning in the control group before (pretest) and after (posttest) with information services. (3) there is a significant difference in student procrastination in learning in the experimental group and the control group who were given treatment. Thus, information services using self-management techniques to reduce student procrastination in effective learning are carried out at SMA Muhammadiyah 01 Medan.